A composite chitosan-gelatin bi-layered, biomimetic macroporous scaffold for blood vessel tissue engineering. (10th February 2017) - Badhe, Ravindra V.; Bijukumar, Divya; Chejara, Dharmesh R.; Mabrouk, Mostafa; Choonara, Yahya E.; Kumar, Pradeep; du Toit, Lisa C.; Kondiah, Pierre P.D.; Pillay, Viness
Highlights: New glycerol plasticized chitosan-gelatine based elastic and flexible scaffold. New method for the development of macroporous, layered, tubular scaffold. Eudragit ® microsphere size based scaffold porosity control. Biocompatible gelatine degrades faster providing immediate space for cell growth. Chitosan offers mechanical strength and degrade slowly allowing cells to replace it. Abstract: A composite chitosan-gelatin macroporous hydrogel-based scaffold with bi-layered tubular architecture was engineered by solvent casting-co-particulate leaching. The scaffold constituted an inner macroporous layer concealed by a non-porous outer layer mimicking the 3D matrix of blood vessels with cellular adhesion and proliferation. The scaffold was evaluated for its morphological, physicochemical, physicomechanical and biodurability properties employing SEM, FTIR, DSC, XRD, porositometry, rheology and texture analysis. The fluid uptake and biodegradation in the presence of lysozymes was also investigated. Cellular attachment and proliferation was analysed using human dermal fibroblasts (HDF-a) seeded onto the scaffold and evaluated by MTT assay, SEM, and confocal microscopy. Results demonstrated that the scaffold had a desirable tensile strength = 95.81 ± 11 kPa, elongation at break 112.5 ± 13%, porosity 82% and pores between 100 and 230 μm, 50% in vitro biodegradation at day 16 and proliferated fibroblasts over 20 days. These results demonstrate that scaffold may be an excellent tubular archetype for blood vessel tissue engineering.